Solving coastal conundrums 28th international conference on coastal engineering : ICCE 2002 : 7-12 July 2002, Cardiff City Hall, Cardiff, UK - Allsop, N. W. H. 1951- (Thomas Telford, 2002)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of twenty-eighth international conference on coastal engineering held in Cardiff on 7-12 July 2002.